Rehabilitation in palliative patients with heart failure and body composition disorders - V. I. Shevtsova; A. A. Pashkova; A. N. Shevtsov; O. N. Krasnorutskaya; Yu. A. Kotova; P. B. Zarechny (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To evaluate the effectiveness of the rehabilitation program for palliative care patients with heart failure (HF) with body composition disorders.Material and methods. The study involved 298 patients (115 men and 183 women; mean age 61 years) with diagnosed HF and indications for palliative care. The patients were divided into clinical clusters using the сhi-square automatic interaction detection. The 1st clinical cluster included patients with sarcopenic obesity (n=69 [23,2%]), the 3rd cluster — patients with cardiac cachexia (n=47 [15,8%]), the 2nd cluster occupies an intermediate position with an isolated disorder of body composition as follows: sarcopenia or obesity, or without these disorders (n=182 [61,1%]). Then, 2 groups (main and control) of 20 people each were formed from each cluster. The main groups of patients underwent a 6-month rehabilitation program with treatment corresponding to the clinical guidelines of the Ministry of Health of the Russian Federation for HF. The control groups of patients underwent only pharmacotherapy.Results. Patients from all control groups had a significant decrease in muscle mass, while in the 1st and 2nd clusters there was an increase in body mass, and in the 3rd cluster — a decrease. The quality of life of patients from the control groups significantly decreased. Patients from the main groups of the 1st and 2nd clusters had a significant increase in muscle mass and a decrease in body weight. In patients of the 3rd cluster, body weight continued to decrease, but muscle mass indices remained stable. The quality of life of patients from the 1st cluster improved in all indices, and in the 2nd cluster — in scale 2. In patients of the 3rd cluster, the quality of life worsened.Conclusion. The rehabilitation program including exercise and a high-protein diet improved the muscle characteristics and the quality of life of palliative patients with HF. At the same time, the greatest effectiveness of the method was demonstrated in patients with sarcopenic obesity (1st clinical cluster), and the least — in patients with cardiac cachexia (3rd clinical cluster).